Pandorina skrinjica - geografski pogledi na prostorske analize v planiranju - Černe, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
Space is a requisite as the air we breathe, the ground on which we stand, we walk over and through it. Human being is with space, he is part of space, he can not be absent form space. To be at all - to exist in any way - is to be somewhere, and to be somewhere is to be with some kind of space. We are always surrounded by space. We live with space, relate to others with it, die with it. Within this context article deals with the problems arising from analytical approach towards the evaluation of different meaning of space.
Keywords: prostor; geografija; geography; regionalno planiranje; spatial planning; prostorsko planiranje; prostorski razvoj; analize